Factors Relating to the Conjunctivitis Preventive Behaviors among Higher Elementary Students in Hang Hong Municipality, Muang District, Sakon Nakhon Province - จำปาจันทร์, จิราภรณ์; ทัศนเอี่ยม, ศศิวรรณ; วรไธสง, ณีรนุช (Ratchaphruek Journal, 2018)
The aim of this research was to explore the factors relating to the conjunctivitis preventive behaviors among higher elementary students.A total population of 243 students who study in Hang Hong municipality. The data were collected by using a questionnaire were created by the researcher. Data was analyzed by using frequency, percentages, mean, standard deviations, Pearson’s correlation coefficients and independent samples test. The results showed that the experience with conjunctivitis and knowledge of conjunctivitis were all positively associated with attitude for conjunctivitis (t-test = 2.281, p-value = 0.023 and r = 0.350, respectively) and students’ attitude was associated with preventive behavior for conjunctivitis (r = 0.278, p-value < .001). This study suggests that local health organization should promote health preventive behavior for conjunctivitis and organize activities to disseminate information on conjunctivitis in the students. The sources of information on conjunctivitis should be developed. Appropriate types of media should be utilized to serve students or people experienced with conjunctivitis is to stimulate students’ attitudes and practices in the prevention of conjunctivitis further.